An overview of the Sources of lex informatica - Namen- Baquero, David (DIXI, 2021)
Objective: The scarce normative developments at the international level and the initiatives related to the harmonization of the law in the electronic field, make necessary its singular legal discipline. The purpose of this paper is to identify the sources of the so-called lex informática.Methodology: The study starts with the definition of lex informatica, then focuses on the alternative forms of regulation applied to computer law and ends with the systematization of the categories on which this new discipline could be built.Conclusion: The research leads to the conclusion that, in view of the need for an appropriate regulation, the possibility of public and private entities interacting through the co-regulation scheme in the consolidation of this normative body should be explored, and that while this is happening, the custom and general principles of law should continue to be used for its development.
Keywords: Self-regulation; co-regulation; sources; lex informatica